Frames of violence and recent history in Simon Stephens' Motortown - Marion Coste (Sillages Critiques)
British theatre is renowned for tackling topical, red-hot events pertaining to immediate history: the war in Iraq, for instance, prompted swift and diverse responses from British playwrights. The representation of recent history will be analysed in this paper through the representation of torture, and more specifically the Abu Ghraib scandal, in Simon Stephens’s Motortown (2006). Written during the 7/7 bombings in London, the play is permeated with the sense of horror associated with the war against terror and the war in Iraq: it blurs the line between the frontlines and the home front, as Danny, a former squaddie, re-enacts on British soil the acts of torture inflicted on prisoners in Abu Ghraib. This paper will show how, drawing on In-Yer-Face aesthetics, the playwright subverts the framing of torture and reflects on the anti-war movement.